1996
DOI: 10.1126/science.274.5294.1906
|View full text |Cite
|
Sign up to set email alerts
|

CD5-Mediated Negative Regulation of Antigen Receptor-Induced Growth Signals in B-1 B Cells

Abstract: A subset of B lymphocytes present primarily in the peritoneal and pleural cavities is defined by the expression of CD5 and is elevated in autoimmune diseases. Upon signaling through membrane immunoglobulin M (mIgM), splenic B lymphocytes (B-2) proliferate, whereas peritoneal B cells (B-1) undergo apoptosis. However, in CD5-deficient mice, B-1 cells responded to mIgM crosslinking by developing a resistance to apoptosis and entering the cell cycle. In wild-type B-1 cells, prevention of association between CD5 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

19
217
3

Year Published

1998
1998
2009
2009

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 283 publications
(239 citation statements)
references
References 36 publications
19
217
3
Order By: Relevance
“…That is, ligation of WC1 with antibody induces dephosphorylation of a wide range of cell cycle regulatory proteins and results in growth arrest [9][10][11], but anti-WC1 antibody also augments proliferation of gd T cells in the autologous mixed leukocyte reaction as well as proliferation induced by anti-CD3 antibody [12]. These data indicate that WC1 can have both positive and negative effects on gd T-cell activation, consistent with the effects of another SRCR family member found on lymphocytes, CD5 [13][14][15].…”
Section: Introductionsupporting
confidence: 57%
See 1 more Smart Citation
“…That is, ligation of WC1 with antibody induces dephosphorylation of a wide range of cell cycle regulatory proteins and results in growth arrest [9][10][11], but anti-WC1 antibody also augments proliferation of gd T cells in the autologous mixed leukocyte reaction as well as proliferation induced by anti-CD3 antibody [12]. These data indicate that WC1 can have both positive and negative effects on gd T-cell activation, consistent with the effects of another SRCR family member found on lymphocytes, CD5 [13][14][15].…”
Section: Introductionsupporting
confidence: 57%
“…That is, ligation of WC1 with antibody induces dephosphorylation of a wide range of cell cycle regulatory proteins and results in growth arrest [9][10][11], but anti-WC1 antibody also augments proliferation of gd T cells in the autologous mixed leukocyte reaction as well as proliferation induced by anti-CD3 antibody [12]. These data indicate that WC1 can have both positive and negative effects on gd T-cell activation, consistent with the effects of another SRCR family member found on lymphocytes, CD5 [13][14][15].Comparison of the cytoplasmic tails of the various WC1 forms reveals the presence of five tyrosines that could be potentially phosphorylated by the members of src family of protein -tyrosine kinases [16,17]. However, subtle sequence variations between WC1.1 and WC1.2 cytoplasmic tails [8,16] could affect intracellular signaling, and thus result in a different outcome following antigen or cytokine stimulation.…”
supporting
confidence: 57%
“…While our report places CD28 along with CD5 and CD2 in a group of molecules that apparently antagonize positive selection, some important differences between these molecules exist. The cytoplasmic domain of CD5 has an immunoreceptor tyrosine-based inhibition motif (ITIM) and has been shown to negatively regulate signaling through both the TCR and BCR [27,29]. In vitro and in vivo studies with anti-CD2 antibodies revealed inhibition of T cell function, including longlasting hyporesponsiveness, that could not be entirely explained simply by blockade of CD2 interactions with its ligand [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…SMI mice have significantly higher percentages of human Ig-expressing peritoneal B cells that express CD5 than do AB29 mice. CD5 is a molecule that modulates BCR signaling, because it acts as a negative regulator in association with Src homology protein-1 phosphatase (55,56). It is expressed on the surface of both human and murine B-1 B cells, and on the leukemic B cells of virtually all patients with CLL (57).…”
Section: Discussionmentioning
confidence: 99%